The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1413-81232017224.28452016
|View full text |Cite
|
Sign up to set email alerts
|

Análise do financiamento e gasto do Sistema Único de Saúde dos municípios da região de saúde Rota dos Bandeirantes do estado de São Paulo, Brasil

Abstract: The national scenario of lack of resources in the Brazilian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
3
0
6
Order By: Relevance
“…The study showed the existence of significant literature on management in PHC, and it is possible to identify several aspects, including difficulties and facilities present in the work of PHC managers, which may contribute to the increase and also to the reduction of their workloads. Management in the healthcare sector has been recognized as fundamental and one of the most significant macro-problems for the implementation of public health policies (95)(96) .…”
Section: Discussionmentioning
confidence: 99%
“…The study showed the existence of significant literature on management in PHC, and it is possible to identify several aspects, including difficulties and facilities present in the work of PHC managers, which may contribute to the increase and also to the reduction of their workloads. Management in the healthcare sector has been recognized as fundamental and one of the most significant macro-problems for the implementation of public health policies (95)(96) .…”
Section: Discussionmentioning
confidence: 99%
“…The Rota dos Bandeirantes health region was selected for this study because of the great heterogeneity of its cities, as well as for the different collection standards and the existence of different models of public health expenditure management 14 . The years from 2009 to 2012 were set for the study for being the last completed period of municipal government management with data available for analysis.…”
Section: Methods Type and Characterization Of The Study Locationmentioning
confidence: 99%
“…O que chama a atenção é que ao comparar o gasto médio per capita com o sus do total de municípios do estado de Mato Grosso, em 2016, (r$ 877,58) com o dos municípios pesquisados, nota-se que o valor de Ponta Porã foi 44,1% inferior à média estadual/anual, o qual se coloca como um dos mais baixos entre os demais municípios do estado. Essa realidade aponta para as desigualdades com os gastos em saúde pública, também observada em outros estudos (Araújo et al 2017;Santos Neto et al 2017). Os orçamentos municipais e o volume das transferências de recursos da União se revelaram determinantes fortemente associados com essas desigualdades no estudo de Santos Neto et al (2017).…”
Section: Projeto De Governounclassified